Metallizing porous scaffolds as an alternative fabrication method for solid oxide fuel cell anodes - Ruiz-Trejo,E; Atkinson,A; Brandon,NP (Journal of Power Sources, 2015)
A combination of electroless and electrolytic techniques is used to incorporate nickel into a porous Ce0.9Gd0.1O1.90 scaffold. First a porous backbone was screen printed into a YSZ electrolyte using an ink that contains sacrificial pore formers. Once sintered, the scaffold was coated with silver using Tollens' reaction followed by electrodeposition of nickel in a Watts bath. At high temperatures the silver forms droplets enabling direct contact between the gadolinia-doped ceria and nickel. Using impedance spectroscopy analysis in a symmetrical cell a total area specific resistance of 1 Ωcm2 at 700 °C in 97% H2 with 3% H2O was found, indicating the potential of this fabrication method for scaling up.